Expanding Work Programs for Poor Men. - Mead, Lawrence M. (Rowman & Littlefield Pub. Group, 2011)
Welfare reform, which required that poor mothers work in return for assistance, was a watershed in the struggle against poverty for American families. As work levels rose dramatically among low-income women, the welfare rolls were cut in half and many families rose out of poverty. But men's employment is also crucial to uplifting families, and programs designed to encourage work among poor men are often poorly funded and little understood by policymakers. Expanding Work Programs for Poor Men makesthe case that poor fathers, like poor mothers, need "both help and hassle." That is, poor men nee.